Sistem Agribisnis pada Budidaya Pembesaran Ikan Patin - Saputra, Anggoro Dwi; Zulkarnain, Zulkarnain (Jurnal Ilmiah Pertanian dan Peternakan, 2024)
Purpose: Research objectives: is to analyze the study of the catfish rearing agribusiness system in Margoerejo Village, South Metro District, Metro City. Method: Respondents in this study amounted to 3 people consisting of 1 cultivator, 1 processor and 1 trader. The research method used is a case study. The data collected includes primary data and secondary data. The analysis carried out includes qualitative descriptive analysis, income analysis, added value and marketing. Results: The results showed that the procurement of feed inputs did not meet the criteria for the right price and right quality. The income from cash costs obtained from catfish cultivation was Rp. 156.343,285 per season with an R/C value of 2.87. The highest added value of processed catfish products is produced by catfish skin crackers with a ratio value of 14.63 percent. The marketing of fresh catfish production in Metro Selatan Urban Village, Metro City is quite efficient, while the marketing of processed catfish is quite good. Conclusions: The study concludes that catfish aquaculture agribusiness involves five subsystems: input supply with minor feed pricing issues, profitable farming with an R/C ratio of 2.87, value-added processing into fish crackers, direct marketing yielding 19.40% profit margin, and supporting services that enhance overall business efficiency. Limitations: The business carried out by fish farmers is only limited to rearing catfish from upstream to downstream Contribution: Fish farmers can run a well-integrated catfish cultivation agribusiness system so that business efficiency can be realized